2013
DOI: 10.1128/aac.01633-12
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin and Chlorhexidine Resistance in Staphylococcus aureus in Patients with Community-Onset Skin and Soft Tissue Infections

Abstract: Decolonization measures, including mupirocin and chlorhexidine, are often prescribed to prevent Staphylococcus aureus skin and soft tissue infections (SSTI). The objective of this study was to determine the prevalence of high-level mupirocin and chlorhexidine resistance in S. aureus strains recovered from patients with SSTI before and after mupirocin and chlorhexidine administration and to determine whether carriage of a mupirocin-or chlorhexidine-resistant strain at baseline precluded S. aureus eradication. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
97
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 48 publications
7
97
5
2
Order By: Relevance
“…Mupirocin resistance may be helpful in the spread of multidrug resistance through co-selection with other resistance genes. Previous reports found that mupirocin-resistant S. aureus isolates were multi-resistant to other antimicrobial agents, such as ciprofloxacin, clindamycin, and tetracycline (21,22). Similarly, in present study, mupirocinresistant S. epidermidis were also multi-drug resistant to other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 61%
“…Mupirocin resistance may be helpful in the spread of multidrug resistance through co-selection with other resistance genes. Previous reports found that mupirocin-resistant S. aureus isolates were multi-resistant to other antimicrobial agents, such as ciprofloxacin, clindamycin, and tetracycline (21,22). Similarly, in present study, mupirocinresistant S. epidermidis were also multi-drug resistant to other antimicrobial agents.…”
Section: Discussionsupporting
confidence: 61%
“…Finally, repeated use of CHG for bathing has not been associated with increasing minimum inhibitory concentrations or development of resistance in exposed bacterial strains. 33 " 36 Our study has some limitations. First, because CHG bathing was part of a clinical care protocol, we cannot speculate on compliance to guidelines; we therefore analyzed our data using an intent-to-treat analysis.…”
Section: Discussionmentioning
confidence: 99%
“…8,[32][33][34][35] MRSA resistance to chlorhexidine lacks a standard definition, but recent reports suggest that resistant strains are rare in the United States. 36,37 A gene encoding a multidrug efflux pump that is active against chlorhexidine has been reported in MRSA, 38 but its clinical significance is not understood. Reduced susceptibility to chlorhexidine has also been reported in gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%